The Men and Women Who Purchase Sex in the United States: Understanding Motives, Practices, and Preferences - Kosloski, Anna E. (Women & criminal justice, 2022)
Understanding the motives, behaviors, demographic characteristics, and deterrence strategies of those involved in purchasing commercial sex have focused on samples of men. Through an online survey of men (n = 381) and women who purchase sex (n = 143) in the United States, this study provides an exploratory examination on the differences of purchasing by gender. While men reported purchasing sexual services at a higher rate, women who purchased were less likely to be in a relationship. No differences in the deterrence of purchasing were found by gender, yet current deterrence strategies were not found to be effective among the sample.